A photoactivatable chemotherapeutic Ru(II) complex bearing bathocuproine ligand efficiently induces cell death in human malignant melanoma cells through a multi-mechanistic pathway. (1st October 2021) - Elias, Maria George; Mehanna, Stephanie; Elias, Elias; Khnayzer, Rony S.; Daher, Costantine F.
Abstract: Photoactivated chemotherapy (PACT) is an emerging strategy for targeted cancer therapy. Strained Ru complexes with pseudo-octahedral geometry may undergo photo-induced ligand dissociation, forming aquated photoproducts that are significantly more cytotoxic compared to the precursor complex. The complexes investigated were the strained complex [Ru(bpy)2 BC]Cl2 (where bpy = 2, 2′-bipyridine and BC = bathocuproine) and its unstrained control [Ru(bpy)2 phen]Cl2 (where phen = 1, 10-phenanthroline). The uptake of [Ru(bpy)2 BC]Cl2, assessed by ICP/MS, started immediately post-incubation and plateaued after 24 h. Active transport was found as the main mode of intracellular transport. Cell viability assays on A375 cells indicated a mean phototoxicity index of 340-fold, and the effect was shown to be primarily mediated by the aquated photoproducts rather than the dissociating ligands. A significant increase in ROS production and DNA damage was also observed. Flow cytometry confirmed the induction of early apoptosis at 48 h that proceeds to late apoptosis/necrosis by 72 h post-treatment. Western blot analysis of pro- and anti-apoptotic proteins revealed that apoptosis was mediated through an interplay between the intrinsic and extrinsic pathways, as well as autophagy and via inhibition of the MAPK and PI3K pathways. In conclusion, this study demonstrates that [Ru(bpy)2 BC]Cl2 is a multi-mechanistic PACT drug which exhibits promising anticancer potential. Graphical abstract: Image 1 Highlights: Intracellular photoactivation of [Ru(bpy)2 BC]Cl2 limits side effects as a prodrug. [Ru(bpy)2 BC]Cl2 induces significant ROS and DNA damage upon photoactivation. Apoptosis is induced via the intrinsic and extrinsic pathways. [Ru(bpy)2 BC]Cl2 photoactivation inhibits MAPK and PI3K pathways. [Ru(bpy)2 BC]Cl2 may involve autophagy-dependent cell death.